The Contextualization of Islamic Law in the Pandemic Period through Fiqhiyyah Rules in the MUI Fatwa No. 14 of 2020 as an Effort to Re-actualize the Concept of Religious Moderation - Abdur Rahman Adi Saputera Putra (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2020)
This paper aims to analyze the efforts to re-actualize the concept of religious moderation during a pandemic through the contextualization of Islamic law by applying the principles of fiqhiyyah in MUI Fatwa No. 14 of 2020. This research applies a descriptive-normative approach, with conclusions using inductive and deductive thinking methods. The results of the study stated that there had been stagnation in the implementation of community diversity during the pandemic by rejecting the recommendation to carry out physical distancing through government regulations and MUI Fatwa No. 14 of 2020, even though this Fatwa is part of the relevant efforts of Islamic law to negotiate with situations and conditions. at the same time adapting to align the text and the context of reality at that time. So through the principles of fiqh which are contained in the substance of the fatwa as a knife of analysis, it is practically clear that Islamic law is an instrument that directs people to the concept of Rahmatan Lil Alamin and in accordance with the principles of Sholihul Likulli at the time of Wal Makan.